Indonesia’s Civil Servants' Performance at Aviation Engineering: Exploration Study - Wirma Yuliana; Anita Maharani; Zainur Hidayah (Integrated Journal of Business and Economics (IJBE), 2020)
This research was conducted with the aim of analyzing the relationship of performance allowances in optimizing the performance of Civil Service Civil Engineering Institute. The method used in this study is a qualitative research method. Sampling or data sources in this study were conducted purposively and for the sample size determined by snowball, interviewing techniques, data analysis using interpretive models and research results emphasizing the meaning of generalization. The results of this study indicate that each flight engineer has a workload of each. The workload is made by each employee based on job descriptions which are then outlined in the form of Employee Work Objectives (KPI). The development of achievement of KPI is one aspect in the Employee Job Achievement component, which is a reference in providing employee performance benefits, in addition to assessing the employee work discipline component. The granting of performance benefits has met the principles of fairness, fair and reasonable, competitive and transparent. Of the several motivations received by employees, performance allowances are considered the most effective to be given because by providing performance benefits employees have the ability to meet more needs, as evidenced by the desire of employees to try to carry out work optimally through efforts to achieve work performance and work discipline. Employees try to carry out the workload contained in the KPI well, carry out at least 2 additional tasks and make timely reports.